PERANCANGAN SISTEM INFORMASI PELAYANAN AD-MINISTRASI PADA KANTOR KELURAHAN KALIGANDU KOTA SERANG - Mochamad Yusuf Romdoni; Ramdani Budiman; Ade Kurniawan (LPPM Unbaja, 2021)
Kaligandu Sub-District Office, Serang City, serves all public administration services that have been listed in the sub-district office, including making an application for an ID card, an application for a family card, and a domicile certificate. However, all administrative services and data storage are still carried out with several stages that are quite complicated and have a long waiting time and other data recapitulation processes take a long time to complete. The form data storage is still in the form of files so that there is often a double data storage and the loss of some files from the residents who have been in the data. The registration process for filling out the submission form is still manual and errors often occur in data entry which causes the filling process to be repeated. With the above problems, a good and integrated system is needed in carrying out business processes based on pre-existing systems, namely by building web-based applications and. The web application is used as a media for managing population data by users in carrying out population services. With a website-based application, it makes it easier for the Village to manage administrative files and data repaitulation in making reports, namely the existence of a print system in accordance with the submission of letters so that the submission data remains in the system, as well as in making reports that are automatically formed according to the number of submissions and in In this system, residents, Rt, Rw, and kelurahan can change residents' data so that if something goes wrong they can change it without having to come to the kelurahan office.